BERTEKUN DALAM PEMBACAAN KITAB SUCI BERDASARKAN 1 TIMOTIUS 4:13 - Manase Gulo (Manna Rafflesia, 2018)
The Bible is the revelation of God which is a lamp for the life of the believer. History shows the survival of the Bible in dealing with the times. Many people have been changed by the Bible. Thus reading the Bible becomes an important part of the life of the believer. Reading the Bible requires perseverance so that the meaning of the Scriptures is understood to be done. Therefore through this article, it gives insight to believers to have perseverance in reading the Scriptures and explain how perseverance is meant in reading the Scriptures.